2010
DOI: 10.1136/bjo.2009.177287
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for retinal vein occlusion and early growth of epiretinal membrane: a possible secondary effect?

Abstract: Intravitreal bevacizumab may be associated with an early growth of ERM in eyes with RVO, although a causative relationship cannot be established. Future randomised clinical trials are necessary to determine the efficacy and safety profile of this novel therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…Recently, it is indicated that maintaining a normal balance between antiangiogenic and proangiogenic VEGFs (VEGF 165/VEGF165b) would be more suitable approach instead of only targeting proangiogenic VEGFs. [3233]…”
mentioning
confidence: 99%
“…Recently, it is indicated that maintaining a normal balance between antiangiogenic and proangiogenic VEGFs (VEGF 165/VEGF165b) would be more suitable approach instead of only targeting proangiogenic VEGFs. [3233]…”
mentioning
confidence: 99%
“…They also reported that intravitreal injection of anti-VEGF agent might suppress VMIAs, including ERM formation. On the other hand, there have been reports of secondary ERM formation after intravitreal anti-VEGF injection [14][15][16] . Anti-VEGF has been reported to cause hypoxia in vascular endothelial cells and increase the expression of connective tissue growth factor (CTGF), which plays an important role in tissue fibrosis and ERM formation 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that non‐selective or pan‐VEGF blockade may be detrimental due to blocking neuroprotective isoforms of VEGF essential in retinal homeostasis, adaptive response to ischaemic insult and prevention of apoptosis . Further, anti‐VEGF mediated decreases in nitrous oxide production by endothelial cells may exacerbate macular ischaemia and reduce collateral formation …”
Section: Treatmentmentioning
confidence: 99%
“…127 Further, anti-VEGF mediated decreases in nitrous oxide production by endothelial cells may exacerbate macular ischaemia and reduce collateral formation. 128,129 Ranibizumab (Lucentis) and off-label bevacizumab (Avastin), both non-selective pan-anti-VEGF agents, have taken the retinal world by storm. Intravenous bevacizumab at the oncologic dosage of 5.0 mg/kg reduces macular oedema and improves VA in neovascular AMD.…”
Section: Treatmentmentioning
confidence: 99%